Pengaruh kepemilikan manajerial, kepemilikan institusional dan kepemilikan keluarga terhadap manajemen laba (earning management) pada perusahaan berkepemilikan ultimat yang terdaftar di bei - Starga Lamora; Vince Ratnawati; Kamaliah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to investigate the effect of managerial ownerships,institutional ownerships and family ownerships components to earnings management on the ultimate ownerships companies in Indonesian Stock Exchange.Data is used in this research is secondary data from monetary data inIndonesian Stock Exchange. The sample method used was purposive sampling. From the all of ultimate ownerships companies listed in the Indonesian Stock Exchange, research sample counted 60 companies that meet criteria. Hypothesis testing is done by using multiple linear regression analysis.The result of this research base on hypothesis test show that managerialownerships and institutional ownerships does not have significant effect with earnings management, while family ownerships have significant effect with earnings management. The magnitude of the effect (Adj R-Square) of managerial ownerships, institutional ownerships, and family ownerships on earnings management was 10,10%. While the remaining 80,90% is influenced by other variables.Keyword: managerial ownerships, institutional ownerships, family ownerships, earnings management, ultimate ownerships.